Overcoming the Ambient Manufacturability‐Scalability‐Performance Bottleneck in Colloidal Quantum Dot Photovoltaics. Issue 35 (5th July 2018) - Kirmani, Ahmad R.; Sheikh, Arif D.; Niazi, Muhammad R.; Haque, Md Azimul; Liu, Mengxia; de Arquer, F. Pelayo García; Xu, Jixian; Sun, Bin; Voznyy, Oleksandr; Gasparini, Nicola; Baran, Derya; Wu, Tom; et al.
Abstract: Colloidal quantum dot (CQD) solar cells have risen rapidly in performance; however, their low‐cost fabrication under realistic ambient conditions remains elusive. This study uncovers that humid environments curtail the power conversion efficiency (PCE) of solar cells by preventing the needed oxygen doping of the hole transporter during ambient fabrication. A simple oxygen‐doping step enabling ambient manufacturing irrespective of seasonal humidity variations is devised. Solar cells with PCE > 10% are printed under high humidity at industrially viable speeds. The devices use a tiny fraction of the ink typically needed and are air stable over a year. The humidity‐resilient fabrication of efficient CQD solar cells breaks a long‐standing compromise, which should accelerate commercialization. Abstract : Blade‐coated, >10% power‐conversion‐efficiency (PCE) lead sulfide colloidal‐quantum‐dot (CQD) solar cells fabricated under ≈65% relative humidity are reported. Moisture inhibits optimal oxygen‐doping of the CQD hole‐transporting‐layer (HTL) in n‐i‐p devices, severely curtailing performance. Oxygen‐doping effectively unpins the HTL Fermi level and smooths the energetic landscape, allowing ambient fabrication of 10.3% PCE blade‐coated devices at industrial speeds, without humidity control and with yearlong stability.